Combating Forced Labour : a Handbook for Employers and Business. Special Action Programme to Combat Forced Labour. - Office, International Labour (International Labour Office, 2008)
This handbook provides guidance material and tools for employers and business to strengthen their capacity to address the risk of forced labour and human trafficking in their own operations and in global supply chains.
Keywords: Employee rights.; Forced labor.; Labor laws and legislation, International.; Business.; Travail forcé.; Affaires.; Personnel -- Droits.; businesses (business enterprises); business (commercial function); BUSINESS & ECONOMICS -- Human Resources & Personnel Management.; Business; Employee rights; Forced labor; Labor laws and legislation, International